2019
DOI: 10.12973/eu-jer.8.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effect of the Integration of Arduino to Electrical Experiments on Students' Attitudes towards Technology and ICT by the Mixed Method

Abstract: In this research, After I have realized some technological applications in the course of general physics laboratory II of the science teacher program, this research aims to examine the effects of the students' attitudes towards technology and the information of the communication technology (ICT) with the mixed method. For this application, after the introduction of Arduino was done, it was used as a measuring instrument in the laboratory; it also used the Fritzing program for circuit diagrams and the e-support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…The results obtained thus support the findings of this study. In accordance with this study, the use of computer based technology support in physics laboratory applications has improved the attitudes of the participants towards communication technologies (Arakliotis, Nikolos, & Kalligeros, 2016;Buluş Kırıkkaya & Başaran, 2019;Çömek & Avcı, 2016;Günbatar & Karalar, 2018;Merino, Ruiz, Fernandez, & Gil, 2016;Numanoğlu & Keser, 2017;Oluk & Korkmaz, 2018;Sohn, 2014). It has been seen that activities based on coding in science courses improve students' skills and achievement (Çömek & Avcı, 2016).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The results obtained thus support the findings of this study. In accordance with this study, the use of computer based technology support in physics laboratory applications has improved the attitudes of the participants towards communication technologies (Arakliotis, Nikolos, & Kalligeros, 2016;Buluş Kırıkkaya & Başaran, 2019;Çömek & Avcı, 2016;Günbatar & Karalar, 2018;Merino, Ruiz, Fernandez, & Gil, 2016;Numanoğlu & Keser, 2017;Oluk & Korkmaz, 2018;Sohn, 2014). It has been seen that activities based on coding in science courses improve students' skills and achievement (Çömek & Avcı, 2016).…”
Section: Discussionmentioning
confidence: 56%
“…In researches carried out with different research designs, technology-supported teaching environments such as Robotics and Arduino positively affect the attitudes, interests, motivations and skills of the students both in cognitive and affective dimensions (Buluş Kırıkkaya & Başaran, 2019). For example, it has been observed that students' attitudes towards information communication technologies have increased in technology-supported physics laboratory (Arakliotis, Nikolos, & Kalligeros, 2016;Buluş Kırıkkaya & Başaran, 2019;Çömek & Avcı, 2016;Günbatar & Karalar, 2018;Merino, Ruiz, Fernandez, & Gil, 2016;Numanoğlu & Keser, 2017;Oluk & Korkmaz, 2018;Sohn, 2014). In addition to that, Sáez-López, Román-González and Vázquez-Cano ( 2016) investigated the use of Scratch between the 5th and 6th grades in Spain and found that high and positive attitudes and motivation emerged due to the use of Scratch.…”
Section: Introductionmentioning
confidence: 99%
“…Arduino is a relatively inexpensive microcontroller that is widely used by teachers [16]. The application of Arduino in basic physics laboratories can affect students' attitudes toward performing group works [17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, instead of bringing ready-made experimental sets to the classroom and using these sets only for data collection, they can make the connection and code Arduinos, which require basic electronic skills, with students in the classroom environment, so that students can achieve very important gains in STEM fields. Studies show that the implementation of such practices in the classroom has significant benefits for students (Hadiati, 2019;Kirikkaya & Basaran, 2019;Lee, 2020).…”
Section: Introductionmentioning
confidence: 99%